when it says substitution, use the value from one equation to solve the other.
y = 2x-1, so the 2nd equation becomes
2x+2(2x-1) = 22
2x + 4x - 2 = 22
6x = 24
x = 4
Using elimination, find ways to make one variable disappear by adding the two equations (or multiples of them)
5x+4y=-83
3x-3y=-12
to get rid of y, multiply the two equations by 3 and 4, and you have
15x+12y = -249
12x-12y = -48
Now add them up, and y is eliminated:
27x = -297
x = -11
Now use that value in either of the original equations to get y:
3x-3y = -12
3(-11)-3y = -12
-33 - 3y = -12
-3y = 21
y = -7
Surely your text has examples of this. If not, google will produce lots of examples and explanations online.
Solve by substitute:
1) y=2x-1
2x+2y=22
Solove by emlimination:
1) 5x+4y=-83
3x-3y=-12
Solve using a method of your choice:
1) x+2y=23
5x+10y=55
2) y=x+1
2x-2y=-2
Please help me I don't understand any of this, it's my second day of school and I already feel like a failure and im on the verge of crying
5 answers
working with formulas
-x+y=-13 and 3x-y=19
-x+y=-13 and 3x-y=19 solve by substitute
Sol
ve by substitude
ve by substitude